A mechanistic model to scale up biophysical processes into geographical size gradients in ectotherms. Issue 6 (8th February 2019) - Rubalcaba, Juan G.; Gouveia, Sidney F.; Olalla‐Tárraga, Miguel A.
Abstract: Aim: Understanding the mechanisms behind broad‐scale gradients in animal body size remains challenging. In contrast to endotherms, the extent to which biophysical properties of ectotherms scale up into interspecific size gradients at macroecological scales remains elusive. Our aim here is to investigate what latitudinal body size gradients are expected to emerge from first biophysical principles regarding heat and water balances in terrestrial vertebrate ectotherms. Location: Nearctic and Western Palaearctic. Time period: Theoretical model under current climatic conditions. Major taxa studied: Terrestrial vertebrate ectotherms. Methods: We developed a biophysical model to derive heat balances and rates of water loss of lizard‐like reptiles and anuran‐like amphibians from microclimatic variables. We projected geographically model predictions for different size classes to explore how body temperature ( T b ) and cutaneous evaporative water loss (EWL) are influenced by body size at macroscales. Results: Large‐bodied ectotherms (over 100 g) attain a slightly higher T b and conserve it for longer than small animals (5 g), owing to the lower convective heat dissipation and their greater thermal inertia. While large animals are more at risk of overheating in warm regions, all organisms, irrespective of body size, are constrained by low temperatures experienced at boreal latitudes. Furthermore, because of the nonlinear decrease in EWL with increasing size, larger size allows reduction of water loss of small wet‐skinned ectotherms in more evaporative environments. Main conclusions: Size differences in heat balance offer a mechanistic explanation for the pattern of increasing body size northwards, as well as for the associated decrease in species richness. Water conservation is also identified as a potential mechanism for larger body sizes in dryer areas in wet‐skinned ectotherms such as amphibians. Moreover, our model reveals nonlinear relationships involving size and optimum states of thermal and hydric functions, accounting for complexities that are unnoticeable by traditional, correlative investigations.